INFLUENCE OF PVC RESIN RATIO (PSM-31 AND OXY-74 ON SYNTETIC LEATHER THICKNESS - Pradita Oktaviani; Yuli Suwarno (Politeknik ATK Yogyakarta, 2024)
Synthetic leather is said to have good quality when it conforms to standards. One that affects the quality of synthetic leather is thickness. The purpose of this study was to determine the effect of the ratio of PSM-31 and OXY 74 PVC resins, especially in the thickness. The method of making PVC Emboss synthetic leather uses single coating foam on a laboratory scale with 100 phr PSM-31: 0 phr OXY 74: 90 phr:10 phr; 80 phr:20phr; 70 phr:30 phr; 60 phr:40 phr; 50 phr:50 phr; 40 phr:60 phr; 30 phr: 70 phr; 20 phr:80 phr; 10 phr:90 phr; 0 phr PSM-31:100 phr OXY 74. The experimental results can be known the formulation variation that gives the best results with a ratio of PSM-31: OXY 74 (60: 40 phr), because it does not experience a decrease in thickness and according to the standard of 1.00-1.05 mm. The PSM-31:OXY 74 (60:40phr) formulation has a vertical tensile strength value of 161.7 N and horizontal 84.28 N and a vertical tear resistance of 40.18 N and horizontal 21.56 N, better than the standard 100 phr PSM-31 formulation. However, the horizontal elongation was 153.21% lower than the standard formulation. The PSM-31:OXY 74 (60:40phr) formulation has better color fastness than the standard formulation with a gray scale assesing and gray scale staining value of 3 while the value for the standard formulation is 1.